Types of tourism and sustainability - Sharma, Geetu; Hussain , Sarfraz (Innovative Research Thoughts, 2017)
The development of tourism must be founded on principles of sustainability, long-term economically, morally and socially acceptable for local people of the locations. There are many kinds of tourism described in the literature as 'sustainables': ecological tourism (ecotourism), green tourism, soft rural tourism, agrotourism, community tourism, solidarity and responsible tourism, all of which oppose conventional mass tourism. According to some experts only tourism is deemed ecological in natural reserves or national parks. A wider notion of environmental tourism refers to the type of responsible travel in natural areas, which helps to environmental conservation and the enhancement of local population circumstances and well-being. Equitable tourism is a sustainable type of tourism that seeks to apply the principles of equitable trade, following a number of criteria, focused on respect for people and their lifestyles, and the sustainability of tourist development in local communities.